2003
DOI: 10.1667/0033-7587(2003)159[0612:cotrot]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Radiotoxicity of Two Alpha-Particle-Emitting Immunoconjugates, Terbium-149 and Bismuth-213, Directed against a Tumor-Specific, Exon 9 Deleted (d9) E-Cadherin Adhesion Protein

Abstract: We investigated the effects of the alpha-particle emitters (149)Tb and (213)Bi coupled to a tumor-specific antibody targeting the mutated delta 9 E-cadherin (d9 E-Cad) on single cells and cell pellets. The d9 mutation of the adhesion molecule E-cadherin is found in 10% of diffuse-type gastric cancers and is not expressed in normal tissue. Human breast cancer cells (MDA-MB-435S) transfected with d9 E-Cad or the wild-type E-cadherin gene were used to study the effects of anti-d9 E-Cad MAb coupled to (149)Tb and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Since efficacy of RIT is directly proportional to the mAb’s binding constant, high RIT efficacy was predicted. It should be noted that in RIT studies where similar antigen levels on the surface of the targeted cells were observed in vitro [22,23], the RIT was nevertheless successful in killing the targeted cells. In the future, use of αemitters should also be explored for IGF2R-targeted RIT of osteosarcoma to counteract the relatively low number of binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Since efficacy of RIT is directly proportional to the mAb’s binding constant, high RIT efficacy was predicted. It should be noted that in RIT studies where similar antigen levels on the surface of the targeted cells were observed in vitro [22,23], the RIT was nevertheless successful in killing the targeted cells. In the future, use of αemitters should also be explored for IGF2R-targeted RIT of osteosarcoma to counteract the relatively low number of binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…disseminated gastric cancer (3). The specific binding of the labeled carrier to single tumor cells or tumor cell clusters and the short path length of a-particles emitted by 213 Bi of only several cell diameters result in a high cytotoxic potential (4,5). 213 Bi (t 1/2 = 46 minutes) is eluted from a 225 Ac/ 213 Bi generator and rapidly coupled to mAbs by the chelator CHX-A…”
Section: Dissemination Of Single Tumor Cells Into the Peritonealmentioning
confidence: 99%
“…It has been conjugated to antibodies and used in mice with colorectal cancer, melanoma as well as other malignancies [17,18]. When compared to 213 Bi in preclinical studies the results were indecisive [19]. Polonium (Po), emits x-rays and can be used in external imaging for bio-distribution studies [20].…”
Section: Terbium (Tb)mentioning
confidence: 99%
“…213 Bi has a half-life of 45.6 minutes and emits an alpha particle of 8 MeV. Additionally, a 440 keV photon emission accompanies 26.5% of 213 Bi decays, allowing detailed biodistribution and dosimetry studies to be performed [19,24,26].…”
Section: Terbium (Tb)mentioning
confidence: 99%